2020
DOI: 10.1002/agg2.20004
|View full text |Cite
|
Sign up to set email alerts
|

Soil biochemical and microbial response to wheat and corn stubble residue management in Louisiana

Abstract: The effects of crop residue on soil conditions depend on the quality and management of the residue. Management practices that do not use physical disturbance (prescribed fire and no-till) were investigated for their potential impacts on soil chemical and biological properties. Surface soil samples (0-5 cm) were collected across no-till and prescribed fire treatments of wheat (Triticum spp.) in 2014 and 2015 and in 2014 in corn (Zea mays L.) stubble residue at 0 h (before management) and at 1 h, 6 h, 24 h, 7 d,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…and nitrogenous fertilizers in a wheat rotation (Triticum aestivum L.) increased NH 4  (ammonium) concentrations by 153%, and relative abundance of saprophytic fungi that contribute to the mineralization of plant compounds, which is important since they form the so-called humus. Humus is a mixture of organic compounds that has positive effects on soils by maintaining physical-chemical structure and providing availability of nutrients; Additionally, the amount of ammonium and beneficial organisms increase significantly with the application of nitrogenous fertilizers [10].…”
Section: Results and Discussion Agricultural Implementation And Veget...mentioning
confidence: 99%
“…and nitrogenous fertilizers in a wheat rotation (Triticum aestivum L.) increased NH 4  (ammonium) concentrations by 153%, and relative abundance of saprophytic fungi that contribute to the mineralization of plant compounds, which is important since they form the so-called humus. Humus is a mixture of organic compounds that has positive effects on soils by maintaining physical-chemical structure and providing availability of nutrients; Additionally, the amount of ammonium and beneficial organisms increase significantly with the application of nitrogenous fertilizers [10].…”
Section: Results and Discussion Agricultural Implementation And Veget...mentioning
confidence: 99%
“…However, comprehensive studies on the effect of these prescribed fires on soil microbial communities are rare. Acree et al ( 2020 ) found a significant decrease in abundance of soil total bacteria, saprotrophic and arbuscular mycorrhizae fungi 6 h after wheat stubble burning, but a recovery was observed 7 days after the treatment. However, they did not measure any changes in soil microbial abundance for corn stubble burning (Acree et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acree et al ( 2020 ) found a significant decrease in abundance of soil total bacteria, saprotrophic and arbuscular mycorrhizae fungi 6 h after wheat stubble burning, but a recovery was observed 7 days after the treatment. However, they did not measure any changes in soil microbial abundance for corn stubble burning (Acree et al, 2020 ). Another study measured the effect of burning in a wheat-lupin-wheat crop sequence on soil biological activities (Alvear et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation